The Correlation of Allergic Rhinitis with Obstructive Sleep Apnea Syndrome (OSAS) in Young Adults - Megawati Sianturi; Dwi Marliyawati; Willy Yusmawan; Kanti Yunika (Faculty of Medicine, Diponegoro University, 2020)
Background: Obstructive Sleep Apnea Syndrome (OSAS) is a breathing disorder during sleep that can cause stopping breathing and trigger dangerous diseases. The main symptoms that can occur in OSAS patients are loud snoring and excessive daytime sleepiness so it can disrupt the quality of life and performance. Allergic rhinitis (AR) is one of the risk factors for OSAS, after age, obesity, sex, neck circumference, and anatomic abnormalities of the airway. Allergic rhinitis can disrupt the quality of sleep patients. Allergic rhinitis patient has a risk of OSAS due to obstruction of the upper airways so airflow to the lungs is obstructed.Objective: To analyze the relationship of allergic rhinitis with the incidence of Obstructive Sleep Apnea Syndrome (OSAS) in young adults.Methods: This study is an observational study with a cross-sectional design. Samples were obtained with a probability sampling method by consecutive sampling. The subject of this study were students of the Faculty of Medicine, Diponegoro University, aged 18-23 years. This study consisted of interviews, BMI examination, neck circumference examination, nose, and throat examination, fill the Epworth Sleepiness Scale (ESS) questionnaire to assess OSAS and the Score For Allergic Rhinitis (SFAR) questionnaire to assess allergic rhinitis. Statistical tests use chi-square, fisher's exact test, and logistic regression.Results: The incidence of allergic rhinitis with OSAS in young adults occurred as much as 79,7%. Bivariate analyze showed allergic rhinitis associated significantly with the incidence of OSAS in young adults (p=0,000; PR=12,3). The most common group of allergic rhinitis symptoms in allergic rhinitis patients with OSAS is the group of symptoms of sneezing, rhinorrhea, and nasal congestion.Conclusion: Allergic rhinitis patients risk 12,3 times more likely to suffer from OSAS than non-allergic rhinitis in young adults.